2016
DOI: 10.17795/ijcp-4516
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care as the Driving Force for Providing Psychological Comfort to Patients with Cancer: A Hermeneutic Study

Abstract: Background: Palliative care is an important part of effective cancer care Objectives: The purpose of our study was to explore the lived experiences of nurses providing psychological palliative care for cancer patients in Iran. Methods: A hermeneutic phenomenological study was performed. We interviewed 11 oncology nurses to understand their lived experiences in cancer wards about psychological palliative care. We employed a seven-stage process of data analysis. Results: One constitutive pattern 'palliative care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Similarly, researchers in Iran declared that psychological PC of patients is done in the form of decreasing tension and empathizing with them. 26 Findings this study revealed that for more effective PC services, it is better to have nurses' cooperation. The present study did not evaluate the concept of PC in one specific kind of cancer and it takes into consideration all kinds of cancers.…”
Section: Theme 3: Psychological Factorsmentioning
confidence: 79%
“…Similarly, researchers in Iran declared that psychological PC of patients is done in the form of decreasing tension and empathizing with them. 26 Findings this study revealed that for more effective PC services, it is better to have nurses' cooperation. The present study did not evaluate the concept of PC in one specific kind of cancer and it takes into consideration all kinds of cancers.…”
Section: Theme 3: Psychological Factorsmentioning
confidence: 79%
“…The important components and findings of final included articles are presented in Table 2 . Results of the study showed that included studies had a focus on different patients/participants including cancer,[ 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] hemodialysis,[ 45 ] heart failure,[ 46 47 ] chronic disease,[ 48 ] chronic pain,[ 49 ] and with anonymous groups. [ 50 51 52 53 54 55 ] Several provinces/cities were engaged in the studies including Tehran,[ 12 13 14 15 17 20 21 24 25 26 29 30 31 32 33 34 35 37 39 40 41 42 43 48 , 51 , 52 Isfahan,[ 22 27 28 …”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] Majority of studies had quantitative approach, including interventional,[ 17 18 19 22 23 29 31 33 35 44 47 49 54 ] descriptive,[ 20 39 41 42 50 53 ] and correlational-analytical. [ 37 45 46 51 ] This was then followed by qualitative[ 12 13 14 15 16 21 24 25 26 27 30 32 34 36 40 43 48 52 ] and mixed methods. [ 28 38 55 ] In quantitative interventional PC studies, a range of medical-surgical,[ 17 18 19 23 29 31 33 37 ] educational,[ 44 49 54 ] and psycho-spiritual[ 22 35 ] managements were used as an independent variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation